From the Studio to the Stage: Bruno Mars, Liveness, and the Out-of-Tune Voice in “Locked Out of Heaven” (2012) - Stévance, Sophie; Lacasse, Serge; Brachet, Marion (Intersections, 2020)
Bruno Mars excels in his live performances. However, the studio version of the song “Locked Out of Heaven,” from his Unorthodox Jukebox album (2012), is distinctly different from his live performances of the piece in its pitch accuracy. How can we address this contrast, beyond the possibilities of negligence, accidents, or even conscious choices? The answer might reside in an analogy between the inaccurate pitch of the studio song and the video clip, where the director, Cameron Duddy, imitates the deficiencies of a VHS cassette, at the same time utilizing the spontaneity of Mars’s live band. According to Sanden, the removal of human imperfections can often make a performance seem less live. After analyzing the live and recorded vocal performances (with the help of re-mediatized performances we found on the internet), Duddy’s video clip, as well as the critical discourse on liveness in popular music, we argue that such a song re-establishes the power balance between the “final” version of the album and the one presented by pop artists on stage: Bruno Mars offers a new take on the consequences of discomorphosis, thanks to a surprisingly parsimonious use of pitch-correction technology within a meticulously produced pop song.